Effect of growing up poor on labor market outcomes: Evidence from Indonesia - Mayang Rizky; Daniel Suryadarma; Asep Suryahadi (Asian Development Bank Institute (ADBI), 2019)
This paper investigates the long-term effect of child poverty on labor market outcomes using a 14-year span of data from the Indonesian Family Life Survey. Our instrumental variables estimation shows that a child who lived in a poor family when aged between eight and 17 years old suffers from an 87% earnings penalty relative to a child who did not grow up in a poor family. The direct effect remains large after we account for a large set of mediators. Depending on the set of mediators that we use, we estimate an earnings penalty of between 85% and 90%. Similarly, we do not find any evidence that receiving various government transfer programs mediates the effect of growing up poor on earnings as adults.
Keywords: J13; I32; J31; 330; child poverty; Indonesia; instrumental variable; labor market outcomes